Oncolytic potential of Newcastle Disease Virus in feline lymphoma cells: an in vitro evaluation - Alves, Talita Gabriela Luna; Xavier, Pedro Luiz Porfirio; Garnica, Taismara Kustro; Rochetti, Arina Lázaro; Qazi, Talal Jamil; Vendramini, Thiago Henrique Annibale; Haddad, Felipe; Munir, Muhammad; Brunetto, Márcio Antonio; Fukumasu, Heidge (Frontiers in Veterinary Science, 2025)
Lymphoma is one of the most prevalent types of feline cancer. It is characterized as a group of diseases that can affect various organs, such as the gastrointestinal tract, kidneys, thymus, and skin. In feline medicine, the search for alternative treatments is of utmost importance, given the significant number of animals that relapse or are unresponsive to conventional chemotherapy treatment. As an alternative to existing modalities of treatment for a variety of cancers, oncolytic viruses have been studied in the last few years. Those viruses possess a unique ability to target and eliminate cancer cells while simultaneously stimulating an immune response against malignant cells, acting as an immunotherapy. Newcastle Disease Virus (NDV) is an avian paramyxovirus that affects both domestic and wild birds, causing symptoms that range from severe to asymptomatic, depending on the viral strain. Less virulent strains are considered safe for use as a vaccine against Newcastle Disease. In the Oncology field, those strains are also being studied to be used as oncolytic virotherapy for mammals, and several results demonstrate their efficacy in vitro and in vivo. The present study aimed to explore the oncolytic potential of Newcastle Disease Virus expressing green fluorescent protein (NDV-GFP) in feline lymphoma cells isolated from a FeLV-positive patient with thymic lymphoma. The NDV-GFP infected, replicated, and induced apoptosis in feline lymphoma cells. Therefore, these results provide preliminary evidence of the oncolytic activity of NDV in feline leukemia virus-induced lymphoma.